Preparation method for recycling and regenerating Zn-doped manganese-sodium-rich electric ternary positive electrode material from waste nickel cobalt lithium manganate positive electrode
By preparing Zn-doped layered nickel-cobalt-manganese oxide-rich sodium-based cathode materials, the problems of resource recycling of waste lithium-ion batteries and lithium resource shortage have been solved, realizing the resource utilization and performance improvement of waste lithium-ion batteries.
Patent Information
- Application Number
- CN202511036091.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-26
- Publication Date
- 2025-10-31
AI Technical Summary
Existing technologies are insufficient for effectively recycling valuable metals such as lithium, cobalt, and nickel from spent lithium-ion batteries, and the shortage of lithium resources is severe. Improper disposal of spent batteries can cause environmental pollution.
Zn-doped layered nickel-cobalt-manganese oxide sodium-rich cathode material was prepared by steps such as separation, leaching, co-precipitation, and high-temperature calcination. The metal ion ratio was adjusted to improve the material's structural stability and electrochemical performance.
It realizes the resource utilization of waste lithium-ion batteries, alleviates the shortage of lithium resources, improves the cycle performance and electrochemical performance of sodium-ion battery cathode materials, and the process is simple, green and environmentally friendly.
Smart Images

Figure CN120878981A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of waste battery recycling technology, specifically relating to a method for recycling and regenerating Zn-doped sodium-ion battery cathode materials from waste ternary lithium-ion battery cathode materials. Background Technology
[0002] The new energy vehicle industry has driven the rapid development of the power battery market, creating vast market opportunities. With the implementation of national industrial policies and the increasing popularity of new energy vehicles and supporting infrastructure, my country's demand for power batteries will maintain rapid growth.
[0003] Lithium-ion ternary lithium-ion batteries, with their high energy density, are primarily used in new energy passenger vehicles. However, the global reserves of valuable metals such as lithium, cobalt, and nickel, which are essential for producing the cathode materials of lithium-ion batteries, are scarce. The rapid growth in lithium-ion battery production has led to shortages of these raw materials. Furthermore, the capacity of lithium-ion batteries gradually decreases during charge-discharge cycles, reaching a point below 80% when they are considered retired. Typically, the service life of a power battery is around 5 years. Retired lithium-ion batteries contain corrosive electrolytes and toxic heavy metals; improper disposal will inevitably cause serious environmental pollution and pose a threat to human health. Waste lithium-ion batteries contain large amounts of valuable metals such as lithium, nickel, and cobalt, which can be extracted and have significant economic value. Therefore, recycling waste lithium-ion batteries not only achieves resource reuse but also brings environmental, economic, and social benefits.
[0004] The surge in lithium-ion battery production inevitably leads to a wave of battery retirements. The continuous consumption of raw materials and the increasing amount of retired batteries have raised concerns about lithium resource reserves. Sodium, a member of the same group as lithium, is abundant, widely distributed, and inexpensive, and sodium-ion batteries share a similar electrochemical mechanism with lithium-ion batteries. Therefore, research on sodium-ion batteries has become a focus of attention.
[0005] Among the various cathode materials for sodium-ion batteries, layered transition metal oxides (Na₂O₃) are the most common. x TMO2 (TM is a transition metal), especially the P2 type, is favored due to its high specific capacity, structural stability, and good rate performance. Manganese-rich P2-type layered transition metal oxides are among the most widely studied oxides, with Mn playing a significant role in stabilizing the structure and offering advantages such as low cost and environmental friendliness. Mn... 3+ / Mn 4+ The low operating voltage of redox reactions, the Jahn-Teller effect, and complex phase transitions lead to a severe degradation in their cycle stability and rate performance. Appropriate cation doping (e.g., Li, Cu) can mitigate this. 2+ Mg 2+ Zn 2+ It has been proven to effectively eliminate TM layer slip and Na +Vacancy sorting enables rapid solid solution reaction, and surface modification is applied to improve surface structure stability during cycling.
[0006] Therefore, this invention prepares a recycled Zn-doped layered nickel-cobalt-manganese oxide sodium-rich cathode material by recycling spent ternary lithium-ion batteries. The cycling performance of the recycled layered nickel-cobalt-manganese oxide sodium-rich cathode material is improved by adjusting the metal ion ratio in the leachate of spent lithium-cobalt-manganese oxide cathode powder and by reducing the charge transfer resistance of the cathode material through Zn doping, maintaining the integrity of the crystal structure, and expanding the interlayer spacing. This invention has a concise process, effectively recovers spent lithium-cobalt-manganese oxide cathodes, and by recycling them into sodium-rich cathode material, it can effectively alleviate the lithium resource shortage problem. Simultaneously, the electrochemical performance of the recycled sodium-rich cathode material is effectively improved through metal cation doping. Results show that the recycled Zn-doped layered nickel-cobalt-manganese oxide sodium-rich cathode material has excellent sodium storage performance and promising application prospects. Summary of the Invention
[0007] This invention prepares a P2-phase layered regenerated Zn-doped manganese-rich sodium cathode material by leaching, co-precipitation, and high-temperature calcination of separated waste nickel-cobalt-manganese oxide cathode powder. The purpose of this invention is to provide a method for preparing Zn-doped layered nickel-cobalt-manganese oxide manganese-rich sodium cathode material from recycled ternary lithium batteries. Simultaneously, addressing the problems of irreversible phase transitions and transition metal dissolution during the cycling process in regenerated layered P2-phase sodium cathode materials, this invention increases the proportion of Mn to stabilize the material structure, reduces irreversible phase transitions, and introduces metal cations to eliminate TM layer slippage and Na+. + The empty space sorting and recycling process is simple, environmentally friendly, and realizes the resource utilization of waste ternary lithium batteries.
[0008] The objective of this invention is achieved through the following technical solution:
[0009] Step 1: Acid Immersion
[0010] A certain mass of waste lithium nickel cobalt manganese oxide cathode powder is placed in a sulfuric acid solution of a certain concentration, and a certain amount of hydrogen peroxide is added for mixing, heating and stirring leaching. Manganese sulfate and cobalt sulfate are added to adjust the proportion of metal ions in the manganese-rich metal ion leaching solution to obtain a manganese-rich metal ion leaching solution.
[0011] Step 2: Co-precipitation
[0012] N2 is continuously passed into the manganese-rich metal ion leaching solution obtained in step one to prevent the oxidation of divalent manganese ions. A certain concentration of ammonia water and Na2CO3 are simultaneously pumped into the above manganese-rich metal ion leaching solution, the pH is adjusted, a certain temperature and time are maintained, the precipitate is filtered and washed with pure water, and then vacuum dried to obtain the precipitate, which is the manganese-rich nickel-cobalt-manganese carbonate precursor.
[0013] Step 3: Calcination
[0014] (1) The manganese-rich nickel-cobalt-manganese carbonate precursor after vacuum drying in step two was mixed with Na2CO3 and ZnO in a certain proportion, and anhydrous ethanol was added for dispersion ball milling for 1 hour to obtain a uniformly dispersed slurry.
[0015] (2) Place the uniformly dispersed slurry obtained in step (1) into a vacuum drying oven and dry it thoroughly to obtain a uniformly mixed powder.
[0016] (3) The uniformly mixed powder obtained in step (2) is subjected to high-temperature calcination in a muffle furnace at a heating rate of 5℃ / min. -1 First, the temperature is raised to 500℃ and calcined for 5 hours, then the temperature is raised to 850-900℃ and calcined for 12 hours to obtain a regenerated Zn-doped layered nickel-cobalt-manganese oxide manganese-rich ternary cathode material.
[0017] Step 4: Application of wide-temperature-range batteries
[0018] The regenerated Zn-doped layered nickel-cobalt-manganese oxide ternary cathode material obtained in step three was used as the active component of the sodium-ion battery cathode. It was mixed with conductive carbon black and binder PVDF in a mass ratio of 8:1:1, ground, and then uniformly coated onto aluminum foil as the cathode. A sodium metal sheet was used as the anode. A 1.0M NaClO4 / EC / DMC / FEC electrolyte was used to assemble a button-type 2025 battery. Hard carbon was mixed with conductive carbon black and sodium carboxymethyl cellulose in a mass ratio of 90:5:5, ground, and then uniformly coated onto copper foil as the anode. This was then matched with the above cathode to assemble a full cell. Alternatively, the manganese-rich ternary cathode obtained in step three, consisting of regenerated Zn-doped layered nickel-cobalt-manganese oxide, is mixed with conductive carbon black and binder PVDF in a mass ratio of 96:2:2, ground, and then uniformly coated onto aluminum foil as the cathode. Hard carbon is mixed with conductive carbon black, sodium carboxymethyl cellulose, and styrene-butadiene rubber in a mass ratio of 95:2:1.5:1.5, ground, and then uniformly coated onto copper foil as the anode. Multiple layers are stacked sequentially in the order of anode, separator, and cathode to assemble a pouch cell.
[0019] The ternary lithium-ion battery cathode material, lithium nickel cobalt manganese oxide, mentioned in step one above, is recycled from waste lithium-ion power battery ternary materials from Xiamen Tungsten New Energy, including LiNi. 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiNi 0.5 Co 0.2 Mn 0.3 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.8 Co 0.1 Mn0.1 O2; the manganese sulfate used to adjust the metal ion ratio is selected from anhydrous manganese sulfate or manganese sulfate monohydrate, and the cobalt sulfate is selected from anhydrous cobalt sulfate or cobalt sulfate tetrahydrate; the amount of hydrogen peroxide added in the manganese-rich metal ion leaching solution is 1-10 vol%, and the sulfuric acid concentration is 0.5-2 M; the ratio of waste ternary nickel cobalt manganese lithium oxide material to leaching solution is 10-60 g / L, the stirring temperature is controlled at 60-80℃, and the leaching time is 0.5-2 h.
[0020] In step two above, the concentration of ammonia water is 0.1–1.0 M, and the concentration of Na2CO3 solution is 0.2–2.0 M. Ammonia water and Na2CO3 of known concentrations are simultaneously pumped into the manganese-rich metal ion leaching solution from step one, the pH is adjusted to 8.0 ± 0.1, the temperature is 40–80 °C, and the mixture is stirred for 4–12 hours.
[0021] In step three above, the ratio of the total amount of nickel, cobalt, and manganese elements in the manganese-rich nickel-cobalt-manganese carbonate precursor to the amount of sodium carbonate, i.e., n (Ni+Co+Mn) :n (Na2CO3) =1:0.335, and the mass of ZnO added is 0.5 to 10 wt.% of the total mass of the manganese-rich nickel-cobalt-manganese carbonate precursor and Na2CO3.
[0022] The Zn-doped manganese-rich sodium ternary cathode material obtained by the above-described preparation method of the present invention is a layered transition metal oxide (Na₂O₃). 0.67 Ni x Co x Mn y Zn (1-2x-y) O2) material, where 7 / 50≤x≤4 / 25, 14 / 25≤y≤33 / 50.
[0023] The present invention relates to the wide-temperature range application of the recycled Zn-doped sodium-rich ternary cathode material obtained by the above-described preparation method of waste lithium nickel cobalt manganese oxide, or the recycled Zn-doped sodium-rich ternary cathode material of the above-described waste lithium nickel cobalt manganese oxide, characterized in that the button-type 2025 battery assembled from the recycled Zn-doped sodium-rich ternary cathode material of the waste lithium nickel cobalt manganese oxide can be stably cycled from -70℃ to 25℃; and the soft-pack battery assembled from the recycled Zn-doped sodium-rich ternary cathode material of the waste lithium nickel cobalt manganese oxide can be stably cycled from -30℃ to 25℃.
[0024] Compared with existing technologies, this invention has the following advantages:
[0025] 1. The recycling and reuse method of waste ternary lithium-ion battery cathode material in this invention has a simple process, is green and environmentally friendly, realizes the resource utilization of waste ternary power batteries, and can be applied on a large scale.
[0026] 2. This recycling method first applies waste ternary battery materials to sodium-ion batteries, achieving short-process recycling while manufacturing a sodium-ion battery cathode material with excellent performance.
[0027] 3. This method utilizes a multi-metal oxide, a synergistic contribution of various metals found in ternary batteries, in the sodium-ion cathode. Addressing the challenges of irreversible phase transitions and transition metal dissolution during cycling in regenerated layered P2-phase sodium-ion cathode materials, the method increases the proportion of Mn to stabilize the material structure and reduce irreversible phase transitions. It also introduces metal cations to eliminate TM layer slippage and Na... + Vacancies sorting reduces the charge transfer resistance of the cathode material, maintains the integrity of the crystal structure, and expands the interlayer spacing, thus improving the problems of small interlayer spacing and slow kinetics in sodium-ion battery cathode materials and enhancing the cycle performance of regenerated layered nickel-cobalt-manganese oxide-rich manganese sodium-ion battery cathode materials. Attached Figure Description
[0028] Figure 1 The high-performance regenerated Zn-doped layered nickel-cobalt-manganese oxide (Na+) obtained in Example 1 is a sodium-rich manganese oxide. 0.67 Ni 0.16 Co 0.16 Mn 0.65 Zn 0.03 XRD pattern of O2 cathode material.
[0029] Figure 2-a , 2-b The high-performance regenerated Zn-doped layered nickel-cobalt-manganese oxide (Na+) obtained in Example 1 is a sodium-rich manganese oxide. 0.67 Ni 0.16 Co 0.16 Mn 0.65 Zn 0.03 SEM image of O2 cathode material.
[0030] Figure 3-a , 3-b These are the high-performance regenerated Zn-doped layered nickel-cobalt-manganese oxides (Na+) obtained in Example 1. 0.67 Ni 0.16 Co 0.16 Mn 0.65 Zn 0.03 Cyclic performance and charge / discharge curves of O2 as a cathode material in sodium-ion batteries at a current density of 0.5C.
[0031] Figure 4-a , 4-b The high-performance regenerated Zn-doped layered nickel-cobalt-manganese oxide (Na₂O₃) obtained in Example 1 is a manganese-rich oxide. 0.67 Ni 0.16 Co 0.16 Mn 0.65 Zn0.03 Rate performance diagram at room temperature when O2 is used as the positive electrode material of sodium-ion batteries.
[0032] Figure 5 The high-performance regenerated Zn-doped layered nickel-cobalt-manganese oxide (Na₂O₃) obtained in Example 1 is a manganese-rich oxide. 0.67 Ni 0.16 Co 0.1 6Mn 0.65 Zn 0.03 Cycling performance of O2 as a cathode material in sodium-ion batteries at different temperatures.
[0033] Figure 6-a , 6-b The high-performance regenerated Zn-doped layered nickel-cobalt-manganese oxide (Na₂O₃) obtained in Example 1 is a manganese-rich oxide. 0.67 Ni 0.16 Co 0.16 Mn 0.65 Zn 0.03 Cyclic performance and charge / discharge curves of a full cell assembled with O2 and a hard carbon anode.
[0034] Figure 7-a , 7-b The high-performance regenerated Zn-doped layered nickel-cobalt-manganese oxide (Na₂O₃) obtained in Example 1 is a manganese-rich oxide. 0.67 Ni 0.16 Co 0.16 Mn 0.65 Zn 0.03 The room temperature and low temperature cycling performance of a pouch cell assembled with O2 and a hard carbon negative electrode. Detailed Implementation
[0035] The following examples illustrate the recycling of waste nickel-cobalt-manganese lithium oxide cathode powder from waste lithium-ion power battery ternary materials from Xiamen Tungsten New Energy, including LiNi. 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiNi 0.5 Co 0.2 Mn 0.3 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.8 Co 0.1 Mn 0.1 O2.
[0036] Example 1
[0037] 1) Take 0.5g of lithium nickel cobalt manganese oxide (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3Add 2 vol% H2O2 to 50 mL of 0.5 M sulfuric acid solution, then add 0.8806 g of MnSO4·H2O. Maintain 80 °C and stir for 2 h to obtain a metal ion leaching solution.
[0038] 2) Nitrogen gas was introduced into the metal ion leaching solution. 10 mL of 0.2 M ammonia solution and 10 mL of 0.8 M Na₂CO₃ solution were simultaneously pumped into the metal ion leaching solution. The pH was adjusted to 8.0 ± 0.1, and the solution was stirred at 60 °C for 12 h to obtain a precipitate. The precipitate was filtered and washed with pure water, then vacuum dried to obtain the precipitate, which is the manganese-rich nickel-cobalt-manganese carbonate precursor.
[0039] 3) The manganese-rich nickel-cobalt-manganese carbonate precursor obtained after vacuum drying is mixed with sodium carbonate in an amount of n... (Ni+Co+Mn) :n (Na2CO3) Mix the components at a ratio of 1:0.335, add 2 wt.% ZnO, mix again, and add anhydrous ethanol as a dispersant. Ball mill for 1 hour, and vacuum dry the uniformly dispersed mixture for later use.
[0040] 4) Place the dried and uniformly dispersed mixture obtained in step 3) in a muffle furnace and heat at 5°C for 5 min. -1 The temperature was increased to 500℃ and calcined for 5 hours, then increased at 5℃ per minute. -1 The temperature was increased to 850℃ and calcined for 12 hours to obtain regenerated Zn-doped layered nickel-cobalt-manganese oxide rich in manganese (Na). 0.67 Ni 0.16 Co 0.16 Mn 0.65 Zn 0.03 O2) Ternary cathode material.
[0041] The regenerated Zn-doped layered nickel-cobalt-manganese oxide (Na₂O₃) prepared in this embodiment is rich in manganese (Na₂O₃). 0.67 Ni 0.16 Co 0.16 Mn 0.65 Zn 0.03 O2) Ternary cathode material, used as the active component of the sodium-ion battery cathode, is mixed with conductive agent carbon black and binder PVDF in a mass ratio of 8:1:1, ground, and then uniformly coated onto aluminum foil as the working electrode (i.e., the positive electrode). Metallic sodium sheet serves as the negative electrode. 1.0M NaClO4 is dissolved in a mixed solvent of EC:DMC = 1:1 (volume ratio), and 5.0wt% FEC is added as the electrolyte to assemble a button-type 2025 battery. Hard carbon, conductive agent carbon black, and sodium carboxymethyl cellulose are mixed and ground in a mass ratio of 90:5:5, then uniformly coated onto copper foil as the negative electrode, and matched with the above-mentioned positive electrode to assemble a full cell. Na... 0.67 Ni 0.16 Co 0.16 Mn0.65 Zn 0.0 3O2 is mixed with conductive carbon black and binder PVDF in a mass ratio of 96:2:2 and then ground evenly and coated onto aluminum foil as the positive electrode. Hard carbon is mixed with conductive carbon black, sodium carboxymethyl cellulose and styrene-butadiene rubber in a mass ratio of 95:2:1.5:1.5 and then ground evenly and coated onto copper foil as the negative electrode. Multiple layers are stacked in the order of negative electrode, separator and positive electrode to assemble a soft pack battery.
[0042] from Figure 1 As can be seen, the P2 phase (Na) was obtained under calcination at 850℃. 0.67 Ni 0.16 Co 0.16 Mn 0.65 Zn 0.03 O2). Figure 2-a Show Na 0.67 Ni 0.16 Co 0.16 Mn 0.65 Zn 0.03 The precursor of O2 is spherical in shape. Figure 2-b Show Na 0.67 Ni 0.16 Co 0.16 Mn 0.65 Zn 0.03 O2 is generally spherical, contains few impurities, and is uniform in size. Figure 3-a , 3-b As can be seen, at a current density of 0.5C, after 100 cycles, the specific capacity remains at 120 mAh g. -1 The capacity retention rate was 80.7%. Multiple charge-discharge plateaus were observed in the charge-discharge curves, corresponding to the redox reactions of manganese, cobalt, and nickel. The charge-discharge curves remained intact after multiple cycles, indicating that the regenerated Zn-doped cathode material (Na₂O₃) exhibited good performance. 0.67 Ni 0.16 Co 0.16 Mn 0.65 Zn 0.03 O2) has good reversibility. (From...) Figure 4-a It can be seen that the regenerated Zn-doped cathode material (Na) 0.67 Ni 0.16 Co 0.16 Mn 0.65 Zn 0.03 O2 exhibits excellent rate capability at room temperature. Figure 4-b It can be seen that even at -40℃, the regenerated Zn-doped cathode material (Na) 0.67 Ni 0.16 Co 0.16 Mn 0.65 Zn 0.03 O2) can still maintain good rate performance. Figure 5 It can be seen that even at -70℃, the specific capacity can still be maintained at 59mAh g. -1 .from Figure 6-a , 6-b It can be seen that the full-cell battery can still operate stably and has great potential for practical applications. As can be seen from 7-a and 7-b, the pouch battery not only operates normally but also operates stably at low temperatures, thus enabling practical applications.
[0043] Example 2
[0044] 1) Take 0.5g of lithium nickel cobalt manganese oxide (LiNi 0.5 Co 0.2 Mn 0.3 Add 2 vol% H2O2 to 50 mL of 0.5 M sulfuric acid solution, along with 1.51 g MnSO4·H2O and 0.35 g CoSO4·4H2O. Maintain the temperature at 70 °C and stir for 1 h to obtain a metal ion leaching solution.
[0045] 2) Nitrogen gas was introduced into the above metal ion leaching solution. 10 mL of 0.2 M ammonia solution and 10 mL of 0.8 M Na₂CO₃ solution were simultaneously pumped into the metal ion leaching solution. The pH was adjusted to 8.0 ± 0.1, and the solution was stirred at 60 °C for 8 h to obtain a precipitate. The precipitate was filtered and washed with pure water, then vacuum dried to obtain the precipitate, which is the manganese-rich nickel-cobalt-manganese carbonate precursor.
[0046] 3) The manganese-rich nickel-cobalt-manganese carbonate precursor obtained after vacuum drying is mixed with sodium carbonate in an amount of n... (Ni+Co+Mn) :n (Na2CO3) Mix the components at a ratio of 1:0.335, add 2 wt.% ZnO, mix again, and add anhydrous ethanol as a dispersant. Ball mill for 1 hour, and vacuum dry the uniformly dispersed mixture for later use.
[0047] 4) Place the dried and uniformly dispersed mixture obtained in step 3) in a muffle furnace and heat at 5°C for 5 min. -1 The temperature was increased to 500℃ and calcined for 5 hours, then increased at 5℃ for 5 minutes. -1 The temperature was increased to 850℃ and calcined for 12 hours to obtain regenerated Zn-doped layered nickel-cobalt-manganese oxide rich in sodium manganese (Na₂O₃). 0.67 Ni 0.16 Co 0.16 Mn 0.65 Zn 0.03 O2) positive electrode material.
[0048] The regenerated Zn-doped layered nickel-cobalt-manganese oxide (Na₂O₃) prepared in this embodiment is rich in manganese (Na₂O₃). 0.67 Ni 0.16 Co 0.16 Mn0.65 Zn 0.03 O2) Ternary cathode material, used as the active component of the sodium-ion battery cathode, is mixed with conductive agent carbon black and binder PVDF in a mass ratio of 8:1:1, ground, and then uniformly coated onto aluminum foil as the working electrode (i.e., the cathode). Metallic sodium sheet serves as the anode. 1.0M NaClO4 is dissolved in a mixed solvent of EC:DMC = 1:1 (volume ratio), and 5.0wt% FEC is added as the electrolyte to assemble a button-type 2025 battery. Hard carbon, conductive agent carbon black, and sodium carboxymethyl cellulose are mixed and ground in a mass ratio of 90:5:5, then uniformly coated onto copper foil as the anode, and matched with the above cathode to assemble a full cell. Na... 0.67 Ni 0.16 Co 0.16 Mn 0.65 Zn 0.0 3O2 is mixed with conductive carbon black and binder PVDF in a mass ratio of 96:2:2 and then ground evenly and coated onto aluminum foil as the positive electrode. Hard carbon is mixed with conductive carbon black, sodium carboxymethyl cellulose and styrene-butadiene rubber in a mass ratio of 95:2:1.5:1.5 and then ground evenly and coated onto copper foil as the negative electrode. Multiple layers are stacked in the order of negative electrode, separator and positive electrode to assemble a soft pack battery.
[0049] Example 3
[0050] 1) Take 0.5g of lithium nickel cobalt manganese oxide (LiNi 0.6 Co 0.2 Mn 0.2 Add 2 vol% H2O2 to 50 mL of 0.5 M sulfuric acid solution, along with 1.94 g MnSO4·H2O and 0.47 g CoSO4·4H2O. Maintain the temperature at 80 °C and stir for 1 h to obtain a metal ion leaching solution.
[0051] 2) Nitrogen gas was introduced into the above metal ion leaching solution. 10 mL of 0.2 M ammonia solution and 10 mL of 0.8 M Na₂CO₃ solution were simultaneously pumped into the metal ion leaching solution. The pH was adjusted to 8.0 ± 0.1, and the solution was stirred at 60 °C for 8 h to obtain a precipitate. The precipitate was filtered and washed with pure water, then vacuum dried to obtain the precipitate, which is the manganese-rich nickel-cobalt-manganese carbonate precursor.
[0052] 3) The manganese-rich nickel-cobalt-manganese carbonate precursor obtained after vacuum drying is mixed with sodium carbonate in an amount of n... (Ni+Co+Mn) :n (Na2CO3) Mix the components at a ratio of 1:0.335, add 2 wt.% ZnO, mix again, and add anhydrous ethanol as a dispersant. Ball mill for 1 hour, and vacuum dry the uniformly dispersed mixture for later use.
[0053] 4) Place the dried and uniformly dispersed mixture obtained in step 3) in a muffle furnace and heat at 5°C for 5 min. -1 The temperature was increased to 500℃ and calcined for 5 hours, then increased at 5℃ for 5 minutes. -1 The temperature was increased to 850℃ and calcined for 12 hours to obtain regenerated Zn-doped layered nickel-cobalt-manganese oxide rich in manganese (Na). 0.67 Ni 0.16 Co 0.16 Mn 0.65 Zn 0.03 O2) Ternary cathode material.
[0054] The regenerated Zn-doped layered nickel-cobalt-manganese oxide (Na₂O₃) prepared in this embodiment is rich in manganese (Na₂O₃). 0.67 Ni 0.16 Co 0.16 Mn 0.65 Zn 0.03 O2) Ternary cathode material, used as the active component of the sodium-ion battery cathode, is mixed with conductive agent carbon black and binder PVDF in a mass ratio of 8:1:1, ground, and then uniformly coated onto aluminum foil as the working electrode (i.e., the cathode). Metallic sodium sheet serves as the anode. 1.0M NaClO4 is dissolved in a mixed solvent of EC:DMC = 1:1 (volume ratio), and 5.0% FEC is added as the electrolyte to assemble a button-type 2025 battery. Hard carbon, conductive agent carbon black, and sodium carboxymethyl cellulose are mixed and ground in a mass ratio of 90:5:5, then uniformly coated onto copper foil as the anode, and matched with the above cathode to assemble a full cell. Na... 0.67 Ni 0.16 Co 0.16 Mn 0.65 Zn 0.03 O2, conductive carbon black, and binder PVDF are mixed and ground in a mass ratio of 96:2:2 and then uniformly coated onto aluminum foil as the positive electrode. Hard carbon, conductive carbon black, sodium carboxymethyl cellulose, and styrene-butadiene rubber are mixed and ground in a mass ratio of 95:2:1.5:1.5 and then uniformly coated onto copper foil as the negative electrode. Multiple layers are stacked in the order of negative electrode, separator, and positive electrode to assemble a soft-pack battery.
[0055] Example 4
[0056] 1) Take 50g of lithium nickel cobalt manganese oxide (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 Add 2.5 L of 0.5 M sulfuric acid solution (O2), add 5 vol% H2O2, and then add 88.06 g of MnSO4·H2O. Maintain 80 °C and stir for 2 h to obtain a metal ion leaching solution.
[0057] 2) Nitrogen gas was introduced into the above metal ion leaching solution. 300 mL of 0.5 M ammonia solution and 300 mL of 1.0 M Na₂CO₃ solution were simultaneously pumped into the metal ion leaching solution. The pH was adjusted to 8.0 ± 0.1, and the solution was stirred at 60 °C for 12 h to obtain a precipitate. The precipitate was filtered and washed with pure water, then vacuum dried to obtain the precipitate, which is the manganese-rich nickel-cobalt-manganese carbonate precursor.
[0058] 3) The manganese-rich nickel-cobalt-manganese carbonate precursor obtained after vacuum drying is mixed with sodium carbonate in an amount of n... (Ni+Co+Mn) :n (Na2CO3) Mix the components at a ratio of 1:0.335, add 6 wt.% ZnO, and add anhydrous ethanol as a dispersant. Ball mill for 1 hour, and vacuum dry the uniformly dispersed mixture for later use.
[0059] 4) Place the dried and uniformly dispersed mixture obtained in step 3) in a muffle furnace and heat at 5°C for 5 min. -1 The temperature was increased to 500℃ and calcined for 5 hours, then increased at 5℃ for 5 minutes. -1 The temperature was increased to 850℃ and calcined for 12 hours to obtain regenerated Zn-doped layered nickel-cobalt-manganese oxide rich in manganese (Na). 0.67 Ni 0.15 Co 0.15 Mn 0.6 Zn 0.1 O2) Ternary cathode material.
[0060] The regenerated Zn-doped layered nickel-cobalt-manganese oxide (Na₂O₃) prepared in this embodiment is rich in manganese (Na₂O₃). 0.67 Ni 0.15 Co 0.15 Mn 0.6 Zn 0.1 O2) Ternary cathode material, used as the active component of the sodium-ion battery cathode, is mixed with conductive agent carbon black and binder PVDF in a mass ratio of 8:1:1, ground, and then uniformly coated onto aluminum foil as the working electrode (i.e., the cathode). Metallic sodium sheet serves as the anode. 1.0M NaClO4 is dissolved in a mixed solvent of EC:DMC = 1:1 (volume ratio), and 5.0wt% FEC is added as the electrolyte to assemble a button-type 2025 battery. Hard carbon, conductive agent carbon black, and sodium carboxymethyl cellulose are mixed and ground in a mass ratio of 90:5:5, then uniformly coated onto copper foil as the anode, and matched with the above cathode to assemble a full cell. Na... 0.67 Ni 0.15 Co 0.15 Mn 0.6 Zn 0.1O2, conductive carbon black, and binder PVDF are mixed and ground in a mass ratio of 96:2:2 and then uniformly coated onto aluminum foil as the positive electrode. Hard carbon, conductive carbon black, sodium carboxymethyl cellulose, and styrene-butadiene rubber are mixed and ground in a mass ratio of 95:2:1.5:1.5 and then uniformly coated onto copper foil as the negative electrode. Multiple layers are stacked in the order of negative electrode, separator, and positive electrode to assemble a soft-pack battery.
[0061] Example 5
[0062] 1) Take 5 kg of lithium nickel cobalt manganese oxide (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 H₂O₂ was placed in 84 L of 2 M sulfuric acid solution, 5 vol% H₂O₂ was added, and 7.868 kg of MnSO₄ was added. The mixture was kept at 80 °C and stirred for 2 h to obtain a metal ion leaching solution.
[0063] 2) Nitrogen gas was introduced into the above metal ion leaching solution. 10 L of 0.5 M ammonia solution and 10 L of 1.5 M Na₂CO₃ solution were simultaneously pumped into the metal ion leaching solution. The pH was adjusted to 8.0 ± 0.1, and the solution was stirred at 60 °C for 12 h to obtain a precipitate. The precipitate was filtered and washed with pure water, then vacuum dried to obtain the precipitate, which is the manganese-rich nickel-cobalt-manganese carbonate precursor.
[0064] 3) The manganese-rich nickel-cobalt-manganese carbonate precursor obtained after vacuum drying is mixed with sodium carbonate in an amount of n... (Ni+Co+Mn) :n (Na2CO3) Mix the components at a ratio of 1:0.335, add 10 wt.% ZnO, mix again, and add anhydrous ethanol as a dispersant. Ball mill for 1 hour, and then vacuum dry the uniformly dispersed mixture for later use.
[0065] 4) Place the dried and uniformly dispersed mixture obtained in step 3) in a muffle furnace and heat at 5°C for 5 min. -1 The temperature was increased to 500℃ and calcined for 5 hours, then increased at 5℃ for 5 minutes. -1 The temperature was increased to 900℃ and calcined for 12 hours to obtain regenerated Zn-doped layered nickel-cobalt-manganese oxide rich in manganese (Na). 0.67 Ni 0.14 Co 0.14 Mn 0.56 Zn 0.16 O2) Ternary cathode material.
[0066] The regenerated Zn-doped layered nickel-cobalt-manganese oxide (Na₂O₃) prepared in this embodiment is rich in manganese (Na₂O₃). 0.67 Ni 0.14 Co 0.14 Mn 0.56 Zn 0.16O2) Ternary cathode material, used as the active component of the sodium-ion battery cathode, is mixed with conductive agent carbon black and binder PVDF in a mass ratio of 8:1:1, ground, and then uniformly coated onto aluminum foil as the working electrode (i.e., the cathode). Metallic sodium sheet serves as the anode. 1.0M NaClO4 is dissolved in a mixed solvent of EC:DMC = 1:1 (volume ratio), and 5.0wt% FEC is added as the electrolyte to assemble a button-type 2025 battery. Hard carbon, conductive agent carbon black, and sodium carboxymethyl cellulose are mixed and ground in a mass ratio of 90:5:5, then uniformly coated onto copper foil as the anode, and matched with the above cathode to assemble a full cell. Na... 0.67 Ni 0.14 Co 0.14 Mn 0.56 Zn 0.16 O2, conductive carbon black, and binder PVDF are mixed and ground in a mass ratio of 96:2:2 and then uniformly coated onto aluminum foil as the positive electrode. Hard carbon, conductive carbon black, sodium carboxymethyl cellulose, and styrene-butadiene rubber are mixed and ground in a mass ratio of 95:2:1.5:1.5 and then uniformly coated onto copper foil as the negative electrode. Multiple layers are stacked in the order of negative electrode, separator, and positive electrode to assemble a soft-pack battery.
Claims
1. A method for preparing Zn-doped manganese-rich sodium ternary cathode material from recycled waste lithium nickel cobalt manganese oxide cathodes, comprising the following steps: Step 1: Acid Immersion A certain mass of waste lithium nickel cobalt manganese oxide cathode powder is placed in a sulfuric acid solution of a certain concentration, and a certain amount of hydrogen peroxide is added for mixing, heating and stirring leaching. Manganese sulfate and cobalt sulfate are added to adjust the proportion of metal ions in the manganese-rich metal ion leaching solution to obtain a manganese-rich metal ion leaching solution. Step 2: Co-precipitation N2 is continuously introduced into the manganese-rich metal ion leaching solution obtained in step one to prevent the divalent manganese ions from being oxidized. A certain concentration of ammonia water and Na2CO3 are simultaneously pumped into the above manganese-rich metal ion leaching solution. The pH is adjusted, and a certain temperature and time are maintained. The precipitate is filtered and washed with pure water, and then vacuum dried to obtain the precipitate, which is the manganese-rich nickel-cobalt-manganese carbonate precursor. Step 3: Calcination (1) The manganese-rich nickel-cobalt-manganese carbonate precursor after vacuum drying in step two was mixed with Na2CO3 and ZnO in a certain proportion, and anhydrous ethanol was added for dispersion ball milling for 1 h to obtain a uniformly dispersed slurry. (2) Place the uniformly dispersed slurry obtained in step (1) into a vacuum drying oven and dry it thoroughly to obtain a uniformly mixed powder. (3) The uniformly mixed powder obtained in step (2) is subjected to high-temperature calcination in a muffle furnace at a heating rate of 5°C. o C min -1 First, heat to 500 o Calcination at C for 5 hours, then heating to 850-900°C o Calcination with C for 12 h yields a manganese-rich ternary cathode material of regenerated Zn-doped layered nickel-cobalt-manganese oxide; Step 4: Application of wide-temperature-range batteries The regenerated Zn-doped layered nickel-cobalt-manganese oxide ternary cathode material obtained in step three was used as the active component of the sodium-ion battery cathode. It was mixed with conductive agent carbon black and binder PVDF in a mass ratio of 8:1:1, ground, and then uniformly coated onto aluminum foil as the cathode. A metallic sodium sheet served as the anode. Using NaClO4 / EC / DMC / FEC as the electrolyte, a button-type 2025 battery is assembled. Hard carbon, conductive carbon black, and sodium carboxymethyl cellulose are mixed and ground in a mass ratio of 90:5:5 and then uniformly coated onto copper foil as the negative electrode. This is then matched with the aforementioned positive electrode to assemble a full cell. Alternatively, the regenerated Zn-doped layered nickel-cobalt-manganese oxide manganese-rich ternary positive electrode material obtained in step three is mixed and ground with conductive carbon black and binder PVDF in a mass ratio of 96:2:2 and then uniformly coated onto aluminum foil as the positive electrode. Hard carbon, conductive carbon black, sodium carboxymethyl cellulose, and styrene-butadiene rubber are mixed and ground in a mass ratio of 95:2:1.5:1.5 and then uniformly coated onto copper foil as the negative electrode. Multiple layers are stacked sequentially in the order of negative electrode, separator, and positive electrode to assemble a pouch battery.
2. The preparation method according to claim 1, characterized in that... In step one, the waste nickel-cobalt-manganese lithium cathode powder is recycled from the waste lithium-ion power battery ternary materials of Xiamen Tungsten New Energy, including LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiNi 0.5 Co 0.2 Mn 0.3 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.8 Co 0.1 Mn 0.1 O2; the manganese sulfate used to adjust the metal ion ratio in the leachate is selected from anhydrous manganese sulfate or manganese sulfate monohydrate, and the cobalt sulfate is selected from anhydrous cobalt sulfate or cobalt sulfate tetrahydrate; the amount of hydrogen peroxide added in the manganese-rich metal ion leachate is 1~10 vol%, and the sulfuric acid concentration is 0.5~2 M; the ratio of waste ternary nickel-cobalt-manganese lithium oxide powder to manganese-rich metal ion leachate is 10~60 g / L. -1 The stirring temperature should be controlled at 60~80°C. o C, leaching time 0.5~2 h.
3. The preparation method according to claim 1, characterized in that... In step two, the concentration of ammonia water is 0.1~1.0 M, and the concentration of Na2CO3 solution is 0.2~2.0 M. Ammonia water and Na2CO3 of known concentrations are simultaneously pumped into the manganese-rich metal ion leaching solution from step one. The pH of the manganese-rich metal ion leaching solution is adjusted to 8.0±0.1, and the temperature is maintained at 40~80°C. o Heat and stir at temperature C for 4-12 hours.
4. The preparation method according to claim 1, characterized in that... In step three, the ratio of the total amount of nickel, cobalt, and manganese elements in the manganese-rich nickel-cobalt-manganese carbonate precursor to the amount of sodium carbonate, i.e., n (Ni+Co+Mn) : n (Na2CO3) =1:0.335, the mass of ZnO added is 0.5~10 wt.% of the total mass of manganese-rich nickel-cobalt-manganese carbonate precursor and Na2CO3.
5. The Zn-doped manganese-rich sodium ternary cathode material for recycling and regenerating waste lithium nickel cobalt manganese oxide cathodes prepared by any one of claims 1-4 is a layered transition metal oxide Na. 0.67 Ni x Co x Mn y Zn (1-2x-y) O2 material, among which, 7 / 50≤x≤4 / 25, 14 / 25≤y≤33 / 50.
6. The wide-temperature-range application of the recycled Zn-doped sodium-rich ternary cathode material from waste lithium nickel cobalt manganese oxide prepared by any of the preparation methods described in claims 1-4, or the recycled Zn-doped sodium-rich ternary cathode material from waste lithium nickel cobalt manganese oxide prepared by claim 5, characterized in that... The aforementioned recycled lithium nickel cobalt manganese oxide cathode material, regenerated from Zn-doped manganese-rich sodium ternary cathode material, can be assembled into a button-type 2025 battery that can operate at -70°C. o C ~ 25 o C-stable cycle; the soft-pack battery assembled from the recycled Zn-doped manganese-rich sodium ternary cathode material of the waste nickel-cobalt-manganese lithium oxide cathode can operate at -30°C. o C ~25 o C stable loop.
Citation Information
Cited By
High-entropy sodium battery cathode material and preparation method and battery thereof
CN122417863A
